(untitled) (International Journal of Environmental Sciences, 2025)
Dyslipidemia is a term used to describe a general elevation of fats in the body’s bloodstream. More specifically, it denotes an elevation of triglycerides and/or total cholesterol or low-density lipoprotein (LDL) cholesterol, and/or a decrease in high-density lipoprotein (HDL) cholesterol. and can accumulate as a result of an imbalance between lipoprotein uptake and secretion in the body’s tissues. (Ofori, 2023 ; Bays et al.,2024) These changes can occur as a result of genetic abnormalities, secondary factors such as diet, alcohol, drugs, and certain medical conditions, Plasma or serum is the only known physiological fluid that can be used to reliably detect dyslipidemia and abnormal lipid levels. (Berberich & Hegele, 2022 ; Chen et al.,2023 ; Yanai et al.,2023). These pieces of evidence undoubtedly suggest the importance of managing dyslipidemia in preventing many diseased condition such as diabetes (Cheng, et al.,2025), atherosclerosis (Laurindo et al.,2025, cardiovascular diseases. (Zakai et al.,2022 ; König et al.,2023 ; Krohn et al.,2023)and alzahaimar ( Kuroda et al., 2025). Obesity now affects many millions of people worldwide, and the incidence of this condition continues to increase. Modern lifestyles, characterized by high-calorie foods and minimal physical activity, are conducive to the development of obesity. Simply put, people are eating more high-fat, energy-dense foods and are getting less physical activity than in years past (Balwan & Kour, 2021 ; Sørensen et al., 2022). Fat intake, particularly saturated and trans fat, is a major dietary contributor to dyslipidemia, and research suggests that this type of diet in obese individuals can lead to an atherogenic lipoprotein profile, impaired vascular function, and an increase in inflammatory and thrombotic markers (Kim et al., 2021 ; Magriplis et al.,2022). In line with the recent ATP III guidelines, there is also interest in triglyceride levels and the prevalence of low HDL in relation to obesity and the metabolic syndrome (Kosmas et al.,2023). It is widely recognized that obesity greatly increases the risk of type II diabetes, and in turn, diabetes is associated with a major dyslipidemic state characterized by increased LDL, VLDL, cholesterol, and triglycerides (Hariharan et al.,2022). Both obesity and dyslipidemia are states of increased oxidative stress, signified by increased production of free radicals, oxidation of lipids, and increased levels of lipid peroxidation products. Increased fatty acid delivery to adipose tissue in obesity results in increased free fatty acid efflux to the liver (Blagojevic et al.,2022). Increased oxidative stress and peroxidation of these fatty acids can result in lipoperoxidation and subsequent production of oxidized, atherogenic LDL. Increased production of inflammatory adipocytokines and cytokines in obesity can up-regulate hepatic production of very-low-density lipoproteins (VLDL) and impair reverse cholesterol transport, also increasing atherogenic oxidized LDL (Čolak & Pap, 2021 ; Blagojevic et al.,2022). The net result is the production of atherogenic dyslipidemia and increased lipid peroxidation.